Longitudinal MRI study on the natural history of carotid artery plaques in symptomatic patients. - Robert M Kwee; Martine T B Truijman; Robert J van Oostenbrugge; Werner H Mess; Martin H Prins; Cees L Franke; Arthur G G C Korten; Joachim E Wildberger; M Eline Kooi (PLoS ONE, 2012)
PURPOSE: To investigate the natural history of carotid atherosclerosis in patients who experienced a TIA or ischemic stroke. PATIENTS AND METHODS: Ninety-two TIA/stroke patients (57 men, mean age 67.7 ± 9.8 years) with ipsilateral <70% carotid stenosis underwent multisequence MRI of the plaque ipsilateral to the symptomatic side at baseline and after one year. For each plaque, several parameters were assessed at both time points. RESULTS: Carotid lumen, wall and total vessel ( = carotid lumen and wall) volume did not significantly change. Forty-four patients had a plaque with a lipid-rich necrotic core (LRNC) at baseline, of which 34 also had a LRNC after one year. In three patients a LRNC appeared after one year. Thirty patients had a plaque with a thin and/or ruptured fibrous cap (FC) at both time points. In seven patients, FC status changed from thin and/or ruptured into thick and intact. In three patients, FC status changed from thick and intact into thin and/or ruptured. Twenty patients had intraplaque hemorrhage (IPH) at both time points. In four patients, IPH disappeared, whereas in three patients, new IPH appeared at follow-up. CONCLUSION: In TIA/stroke patients, carotid plaque morphology does not significantly change over a one-year period. IPH and FC status change in a minority of patients.